Social Loafing On Students Of Muhammadiyah University Sidoarjo: Sosial Loafing Pada Mahasiswa Universitas Muhammadiyah Sidoarjo - Ranti Jihan Oktrivia; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2021)
This problem is motivated by the phenomenon of social loafing among students of the Muhammadiyah University of Sidoarjo. Social loafing is a lack of individual effort when working simultaneosly compared to when perfoming individual tasks. The purpose of this study was to determine the description of social loafing and the factors that cause students of the University of Muhammadiyah Sidoarjo to do descriptive quantitative social loafing. The population in this study were 9469 students of the University of Muhammadiyah Sidoarjo who were involved in the social loafing response at the University of Muhammadiyah Sidoarjo. The sample used was 355 students based on an error rate of 5% in the table developed by Isacc and Michael. The data collection technique in this study uses a psychological scale, which is a social loafing scale in the form of a used scale. Based on the results of the validity test 15 valid items from the 44 compiled items. The reliability test showed a value of (r = 0.919). Based on the results of the analysis showed that the high category of social loafing (15.5%), medium (68.4%) and low (16.1). Most of the factors that influence social learning are no evaluation or assessment of group performance. The social loafing factor is obtained when there is no individual contribution between groups and the unclear division of responsibilities.